2012
DOI: 10.1016/j.scitotenv.2012.04.038
|View full text |Cite
|
Sign up to set email alerts
|

Effect of olive-mill waste addition to soil on sorption, persistence, and mobility of herbicides used in Mediterranean olive groves

Abstract: Laboratory and field experiments were conducted to evaluate the effect of olive-mill waste (OMW) addition to a Mediterranean olive grove soil on sorption, persistence, and mobility of two herbicides which are simultaneously applied for weed control in olive groves: terbuthylazine (TA) and fluometuron (FM). Laboratory batch sorption experiments showed that OMW addition to the soil at rates of 5 and 10% (w/w) greatly enhanced the sorption of both herbicides, thus suggesting that amendment with OMW could be usefu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 42 publications
3
9
0
1
Order By: Relevance
“…Sorption of metalaxyl by both soils was found to be non-enantioselective, that is, the two enantiomers were sorbed to the same extent, and the addition of the amendments did not affect the non-enantioselective character of metalaxyl sorption in the soils tested. These results agree with previous sorption studies of rac-metalaxyl on soils and soil components G amiz et al, 2013;Sukul et al, 2013).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Sorption of metalaxyl by both soils was found to be non-enantioselective, that is, the two enantiomers were sorbed to the same extent, and the addition of the amendments did not affect the non-enantioselective character of metalaxyl sorption in the soils tested. These results agree with previous sorption studies of rac-metalaxyl on soils and soil components G amiz et al, 2013;Sukul et al, 2013).…”
Section: Resultssupporting
confidence: 93%
“…3, Table 2). This result has previously been observed by G amiz et al (2013) in a soil very similar to our soil 2 amended with ALP, and was attributed to changes in microbial populations after amendment, the presence of a new C or energy source for microorganisms, and/or some toxic effects of ALP on metalaxyl degraders, as suggested for other pesticides after amending soil with fresh olive-mill wastes (Fernandes et al, 2006;G amiz et al, 2012;Peña et al, 2015). In soil 2 amended with ALP, both the value of EF at the end of the incubation period (EF ¼ 0.60) and the ES factor (ES ¼ 0.27) confirmed that enantioselectivity in metalaxyl dissipation was less pronounced than in unamended soil (EF ¼ 0.83, ES ¼ 0.74), because the degradation patterns of the two enantiomers became more similar.…”
Section: Dissipation In Alp-and Alpceamended Soilssupporting
confidence: 90%
“…This low density was attributed to some soil disturbance upon sampling, as the 0-5 cm soil section in the sampling spade was visually less compacted than deeper soil sections. The slightly higher initial fungicide concentrations observed for clay-and BCamended soil compared to unamended soil (significant for metalaxyl) could also reflect slight differences in soil density after amendment, as previously suggested for organically-amended field soils (Gámiz et al, 2012). On the other hand, since soil concentration data were simultaneously influenced by fungicide degradation and transport losses, to evaluate leaching we calculated the fraction of residues at different soil depths relative to the total amount extracted from the 0-20 cm soil profile.…”
Section: Fungicide Persistence and Leachingsupporting
confidence: 61%
“…The use of soil organic amendments [8][9][10][11][12][13][14] can reduce drift of some pesticides from one compartment to other in agricultural soils by increasing its sorption, previously recognized as one of the main processes determining the behaviour of pesticides in soils [15].…”
Section: Introductionmentioning
confidence: 99%